Functional indicators of the female athlete's body specializing in rowing - Volodymyr Bogush; Sergiy Getmantsev; Konstantin Bogatyirev; Oksana Reznichenko; Volodymyr Kosenchuk; Oleg Verteleckiy; Yuriy Kulakov (Kharkiv State Academy of Physical Culture, 2019)
Purpose: to conduct a comprehensive study of the functional state of female athlete's specializing in rowing, for the subsequent determination of the prospects in this sport. Material & Methods: girls of various age groups and sports qualifications were examined. The functional state of the athletes was studied according to the developed methodology for measuring the effect of the training action, and the sensorimotor reactions to sound and light stimuli, the power of forced inspiration and expiration, the level of muscular-articular sensitivity and coordination of movements were determined. The testing process simulated typical conditions of training and competitive activity. Results: on the basis of comprehensive studies, it is shown that the most important methodological condition for the formation of a rational technique is the interconnection and interdependence of the structure of movements and the development of physical qualities. Correspondence of an athlete's physical preparedness to the level of possession of sports equipment, structure and the degree of perfection of its characteristics determines the technical preparedness in sports. The proposed research methodology and comparative analysis of average values, as well as relative deviations of the functional state indicators of the examined athletes, may indicate the level of sports preparedness of the rowers. Conclusions: the use of the proposed methodology will maximize focus on the individual characteristics and abilities of each particular athlete when choosing a sports specialization, developing a system of multi-year training, determining the rational structure of training and competitive activity.